PENGARUH SISTEM BERBASIS AKRUAL, TI, DAN SPIP PADA KUALITAS LAPORAN KEUANGAN DENGAN KOMPETENSI SDM SEBAGAI MODERASI - Agustiawan, Nyoman Triyadi; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study was conducted to examine the effect of applying accrual-based accounting system, the use of information technology, and the Internal Control System with the competence of human resources as a moderating variable in the quality of financial reporting. Methods of data collection techniques in this study using a questionnaire. The number of samples in the study were 132 employees in the finance department were selected based on purposive sampling method. The analysis technique used is Moderated Regression Analysis (MRA). The results showed the application of Accrual Based Accounting System, use of information technology and internal control system of government a positive effect on the quality of financial reporting. Other results show the competence of human resources capable of amplifying the effect of the application of accrual-based accounting system, the use of technology, and internal control system on the quality of financial statements.
Keywords: human resource competencies, accrual-based accounting system, information technology, internal control, quality of financial reporting